Vitamin D status among healthy adults in Albania aged 18–35 years: Associations with biological and seasonal factors - Bozo, Silvi; Pojani, Eftiola; Hoxha, Irida Ikonomi; Lami, Bertina Hoxha; Bozo, Dhurata (Edelweiss Applied Science and Technology, 2026)
Vitamin D insufficiency remains a global public health concern, and population-based data from Albania are scarce, particularly among young adults. This study aimed to assess vitamin D status and serum 25-hydroxyvitamin D [25(OH)D] concentrations among healthy Albanian young adults and to examine associations with age, gender, and season of sampling. A cross-sectional study was conducted between January 2023 and January 2025, including 467 healthy adults aged 18–35 years. Serum 25(OH)D concentrations were measured using standardized laboratory procedures in an ISO-certified laboratory. Vitamin D status was classified using a cutoff value of <20 ng/mL. Statistical analyses were performed using SPSS version 27.0. The mean serum 25(OH)D concentration was 25.16 ± 10.30 ng/mL. Overall, 31.7% of participants had concentrations below the study cutoff. Males showed significantly higher mean 25(OH)D levels than females (p < 0.001), while no association was observed with age. Significant seasonal variation was noted, with higher levels in summer and autumn and lower levels in winter and spring (p < 0.001). A considerable proportion of healthy young adults in Albania exhibit suboptimal vitamin D status. Gender and seasonal factors significantly influence serum 25(OH)D concentrations, underscoring the need for targeted public health interventions.